Experimental Study Of Second Semester Student Knowledge About Vital Sign at AKBID Helvetia Medan - Hana Dhini Julia Pohan (International Archives of Medical Sciences and Public Health, 2022)
Midwives have many ways to monitor client well-being. A group of skills that involves measuring physical characteristics as observations, one of which is measuring blood pressure, pulse, respiratory rate and measuring temperature. Can be used to monitor the response of the mother's body to pregnancy, labor, and delivery. The purpose of this study was to determine the difference in knowledge of second semester students about vital signs before and after being given learning media through audio-visual media. The design used in this study was a quasi-experimental study with a non-randomized pretest-posttest control group design that conducted a pretest before treatment was given and posttest afterward, to determine whether there was a difference between the experimental group and the control group. This study used the total population method, where the entire population was sampled as many as 117 respondents. The data used in this study are primary data, secondary data, and tertiary data. The results of this study, the knowledge of students in the intervention group with the Chochran test analysis. Based on the test statistics, the results of the Chochran test showed a significance value of 0.000 from the results of the study (test statistics), the results of the McNemar test obtained a difference in the level of knowledge between the two measurements. Knowledge of students in the control group. Based on test statistics, the results of the Chochran test with a significance value of 0.607 from the results of the study (test statistics), the results of the McNemar test showed no difference in the level of knowledge between the two measurements. Suggestions are expected that audio visual media learning media can increase students' knowledge about vital signs and can be an effective learning media.